1998
DOI: 10.1037/0022-006x.66.4.604
|View full text |Cite
|
Sign up to set email alerts
|

Screening and brief intervention for high-risk college student drinkers: Results from a 2-year follow-up assessment.

Abstract: This randomized controlled trial evaluated the efficacy of a brief intervention designed to reduce the harmful consequences of heavy drinking among high-risk college students. Students screened for risk while in their senior year of high school (188 women and 160 men) were randomly assigned to receive an individualized motivational brief intervention in their freshman year of college or to a no-treatment control condition. A normative group selected from the entire screening pool provided a natural history com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
658
3
15

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 705 publications
(723 citation statements)
references
References 27 publications
44
658
3
15
Order By: Relevance
“…Throughout a 2-year follow-up, the classroom and brief intervention conditions yielded statistically similar reductions over baseline (from 24.4 to 15.0 and 27.2 to 22.0 drinks per week (DPW), respectively). In a second study, Marlatt et al (1998) randomized a group of atrisk freshmen to receive an individual BASICS session or assessment only. After 1 year, BASICS students were mailed additional feedback on their current drinking patterns and, if deemed at high risk, were contacted by phone for a brief motivational session.…”
Section: In-person Feedback Applicationsmentioning
confidence: 99%
“…Throughout a 2-year follow-up, the classroom and brief intervention conditions yielded statistically similar reductions over baseline (from 24.4 to 15.0 and 27.2 to 22.0 drinks per week (DPW), respectively). In a second study, Marlatt et al (1998) randomized a group of atrisk freshmen to receive an individual BASICS session or assessment only. After 1 year, BASICS students were mailed additional feedback on their current drinking patterns and, if deemed at high risk, were contacted by phone for a brief motivational session.…”
Section: In-person Feedback Applicationsmentioning
confidence: 99%
“…There have been many efforts to reduce problematic drinking among college students, with no published reports of interventions to improve contraception among college women. Heavy-drinking high school seniors who received a motivational intervention showed decreased drinking and lower levels of negative consequences of drinking 2 years later (Marlatt et al, 1998). Baer et al (1992) found that a single session of individualized feedback and professional advice using a motivational counseling style produced 40% reductions in drinking for 2 years among young adults.…”
Section: Introductionmentioning
confidence: 99%
“…One interpretation of this consistent lack of effectiveness is that risky drinking represents not a lack of knowledge but rather a lack of motivation to change. Therefore, interventions that enhance motivation for risk reduction are needed to assist the students who are already drinking heavily.Several published studies indicate that in-person brief motivational interventions (BMIs) lead to reduced drinking in college students (Baer et al, 1992;Borsari & Carey, 2000;Larimer et al, 2001;Marlatt et al, 1998;Murphy et al, 2004;Murphy et al, 2001). These BMIs typically consist of one or two 45-min sessions that provide personalized feedback and incorporate motivational interviewing (Miller & Rollnick, 2002).…”
mentioning
confidence: 99%